Pro-Nicene prosopology and the church in Augustine's preaching on John 3:13 - Ployd, Adam (Scottish journal of theology, 2014)
John 3:13 presents a grammatical and theological problem for Augustine. If the only one who ascends to heaven is the one who descended, namely Christ, then what becomes of the Christian life of ascent? To unpack Augustine's solution to this problem, this article explores his use of John 3:13 in his anti-Donatist sermons of 406–7. Here Augustine uses the grammatical method of prosopological exegesis both to identify and to solve the problem of Christ's solo ascent. Prosopology asks of a text, ‘Who is speaking? To whom is he speaking? And about whom is he speaking?’ in order to parse the sometimes ambiguous personae within a dramatic scene. Through this method, Augustine affirms that Christ is indeed speaking about himself alone, but the reflexive subject of Christ includes the church who is his body. The Christian life of ascent to God requires that we become participants in the subject of Christ's ‘I’. Building on the work of ‘New Canon’ Augustine scholarship, I argue that this use of John 3:13 to espouse the unity of the church in the body of Christ is founded upon a pro-Nicene understanding of the revelatory and epistemological role of the Son. The ability of Christ fully to reveal the Father is a central tenet of Latin pro-Nicene refutations of homoian christologies, and this revelation of the Father's Word through Christ's incarnation is accomplished in our union with that Word through his body. Based on this pro-Nicene affirmation of epistemological salvation through Christ, Augustine then uses John 3:13 to condemn the Donatists for damning themselves by separating from the body of Christ. The oneness of the ecclesial body of Christ is predicated upon the oneness of Christ himself because it is into his complex subject that we are incorporated. Separation from that unity is separation from the singular grammatical subject who ascends as Christ to the Father. Thus, Augustine's grammatical practice of prosopological exegesis to solve the problem of John 3:13 connects the pro-Nicene affirmation of Christ's revelation of the Father to an anti-Donatist defence of the necessary unity of the church. This should encourage us to consider further the ways in which pro-Nicene principles help to shape Augustine's vision of the church.